THE BLUE GREEN PATINA ON SCULPTURES CAST IN COPPER AND ITS ALLOYS - THEIR CHEMISTRY AND AESTHETICS - Chawla, Aashu; Sharma, Giriraj (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Copper and its alloys have a tendency to naturally corrode and form a blue green finish over them. This blue green finish has been observed in everyday copper and bronze utensils and even in famous sculptures like statue of liberty. Artists have long taken advantage of this patina to achieve aesthetic of desolateness, age, and damage. This patina tends to change the luster of the metal from reflective to matt and color from pink (gold in case of brass and bronze) to bright blue or green. Artists are known to use this change to add to visual language of their sculptures. The current paper takes in account the whole spectrum of blue – green patinas, from bright blue azurites to dull green verdigris and also dark green copper chloride salts. The paper discusses the chemistry behind the formation of this patina, tests age old recipes and discusses aesthetics with respect to famous Indian sculptors.